Applications of Semantic Similarity Metrics - Parveen, Suraiya; Bisswas, Ranjit (International Journal of Computer Sciences and Engineering, 2025)
The objective of this work is to access the applicability of the semantic similarity in concepts of a single ontology. The measurement of semantic similarity may help not only in information retrieval, but in other applications such as semantic search and semantic clustering. The traditional key-word search technique matches the keyword with the content of the document. These techniques do not reflect the meaning or relatedness. Hence the relevance and accuracy of the retrieved documents are less. Another important application of semantic similarity measurement is in cluster analysis. The semantic clusters may be treated with same function to accomplish the perfect analysis and decision making